South African Native Taxation - Trevor, Daphne (Review of Economic Studies, 1936)
Journal Article South African Native Taxation Get access Daphne Trevor Daphne Trevor London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 3, Issue 3, June 1936, Pages 217–225, https://doi.org/10.2307/2967629 Published: 01 June 1936